Evaluation of Restless Legs syndrome and growing pains in children with familial Mediterranean f - Özge Altuğ-Gücenmez; Balahan Makay; Ayla Kaçar; Erbil Ünsal (The Turkish Journal of Pediatrics)
Growing pains (GP) and restless leg syndrome (RLS) are one of the frequently seen pain syndromes of childhood. These two pain syndromes -GP and RLS- may be confused with exertional leg pain (ELP) of familial Mediterranean fever (FMF). The aim of this study was to evaluate the frequency of fulfilling the criterion for GP and RLS among children with FMF. Sixty FMF patients and 70 healthy controls were enrolled. Clinical and demographic data of patients were recorded. A questionnaire including the symptoms of GP and RLS were applied to all participants and their parents. Twenty-seven patients (45%) had ELP. Ten FMF patients and 10 healthy children fulfilled GP criteria. There was not a significant difference between patients and controls regarding GP. Three FMF patients and 7 healthy controls fulfilled RLS criteria. There was not a significant difference between two groups regarding RLS. Two out of 27 FMF patients with ELP had RLS while one out of 33 FMF patients without ELP had RLS. Eight out of 27 FMF patients with ELP fulfilled GP criteria while two out of 33 FMF patients without ELP fulfilled GP criteria (p=0.01). There was a significant inverse correlation with FMF severity score and GP (p=0.003 and r=-0.376). There was not a significant association with FMF severity score and RLS. This study suggested that GP and RLS are not more common in pediatric FMF patients than their healthy peers.